(3JWHjb GdbGfhf GdLfGFi ai Xd EYdGf MGdI GdWhGQF (B/ s - (3HSGe RGgQ YHO GdQMef NOjhi s; (3YeQ eMeO eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3GdYOd eHJZi GdEfSGf efP cGf(B: (3Edjg cGf OGFeG SYjg(B: (3hef CLdg cGf hSjXd caGMg jfTOg GdeJfGRYhf HSdhc SHjd GdJQGVj(B: (3aEPG CNab SYjge de jcf HO ef hdhL HGH GdJbGVj(B: (3jHJZhf GdfUaI ef GdbVGA ajdhPhf Hg eWeFfjf(B: (3JedCge GdKbI aj GdMUhd Ydi Mbhbge(B: (3EYeGdG dbhGYO bGfhfjI JJSe HGdYehejI hGdJLQjO JVe TFhf GdeLJeY(B: (3hJJUOQ hSGFd GdVHW GdGLJeGYj ajg(B. (3hJfgV OYGFe GdYOd ajeG JfgV Ydi GMJQGe Mbhb GdEfSGf aj GdMQjI hGdeSGhGI hGdYOGdI hGMJQGe Mbhb GdEfSGf Ydi gPG GdfMh bOje bOe GdHTQjI(B: (3hgh jSjQ HGdJSGhj eY JWhQ GdMVGQGJ hfehgG(B. (3aef Mb GdEfSGf Cf jJeJY HMbhb CSGSjI adG jLhR ddJTQjYGJ GdhVYjI Ch deeGQSGJ GdMGce Cf JNGdagG Ch JYJOj YdjgG Ch JfbU efgG hEPG cGf GdEfSGf gh gOa GdMeGjI GdLfGFjI hZGjJgG OGNdjI cGfJ Ce OhdjI HSHH EfSGfjJg Ch HUaJg EfSGfG(B: (3aEf Mbhbg GdJj NhdgG dg HUaJg EfSGfG JTcd eMdG dgPg GdMeGjI(B. s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj , (B2017s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B284-297s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdYOds; (3bGfhf GdWhGQFs; (3MGdI GdWhGQF s; (3LQGFe GdbGfhf GdYGes; (3GdJTQjYGJ GdLfGFjI GdNGUIs; (3EYdGf MGdI GdWhGQFs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs